2012
DOI: 10.1083/jcb.201207047
|View full text |Cite
|
Sign up to set email alerts
|

Local phosphocycling mediated by LOK/SLK restricts ezrin function to the apical aspect of epithelial cells

Abstract: Local cycling of LOK/SLK-dependent phosphorylation of ezrin is required for its apical localization and for microvillus formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
174
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(210 citation statements)
references
References 61 publications
16
174
2
1
Order By: Relevance
“…The kinases Akt2, LOK and SLK, which have been implicated in phosphorylation of ezrin, localize to the apical plasma membrane domain (Shiue et al, 2005;Viswanatha et al, 2012). For other kinases, the localization is less clear.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The kinases Akt2, LOK and SLK, which have been implicated in phosphorylation of ezrin, localize to the apical plasma membrane domain (Shiue et al, 2005;Viswanatha et al, 2012). For other kinases, the localization is less clear.…”
Section: Resultsmentioning
confidence: 99%
“…Various kinases can phosphorylate ezrin and stimulate microvilli development in intestinal epithelial cells and, evidently, these kinases need to be in close proximity to ezrin. Some of these kinases, such as LOK, SLK and Akt2, have been demonstrated to localize in the microvilli membrane at the apical surface (Shiue et al, 2005;Viswanatha et al, 2012), whereas the localization of other kinases, notably aPKCi and Mst4, was not clear. Here, we demonstrated that aPKCi-T555 (as well as its activating kinase PDK1) and Mst4, previously demonstrated to contribute to apical T567 phosphorylation and localization of ezrin and consequently to apical microvilli formation in intestinal epithelial cells (Wald et al, 2008;ten Klooster et al, 2009;Gloerich et al, 2012), did not localize predominantly to the apical surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LOK deficiency also leads to increased LFA-1-mediated lymphocyte adhesion (11). In epithelial cells, localized ezrin phosphorylation by LOK contributes to restricted formation of microvilli at the apical surface (12).…”
mentioning
confidence: 99%